Analyzing orocraniofacial structures for sex estimation using advanced imaging technologies in forensic odontology: a review (Bulletin of the International Association for Paleodontology, 2025)
Determining an individual's sex plays a vital role in their identification within forensic investigations. In determining sex especially in cases such as mass disasters, criminal acts, or conditions where visual identification is not possible, teeth and orocraniofacial bones can be used for the identification process due to their resistance to destruction or decomposition. Some parts of the skull that can be used to identify gender in unidentified victims include the mandible (measured from its mandibular ramus height, condylar mandible), maxillary sinus, mastoid process, foramen magnum. Nowadays, the use of advanced imaging in identifying sex as a non - invasive evaluation process during forensic investigation has been used to obtain more accurate information, such as Cone-Beam Computed Tomography (CBCT), Computed Tomography (CT), Magnetic Resonance Imaging (MRI), and Facial Reconstruction. The advantages of anatomical imaging applications with advanced imaging technique make it easier to be stored for a longer period of time, faster, and easier portability. In addition, Cone Beam Computed Tomography (CBCT) also offers accurate details of complex anatomical structures due to its ability for fast volumetric imaging with high resolution. Sex estimation through advanced imaging techniques using both morphometric and non-morphometric methods show size differences in male and female skulls. This study discusses an overview of the various methodologies and characteristics of advanced imaging techniques for sex estimation in craniofacial region and concludes that advanced imaging is a potential tool in forensic odontology for sex estimation, with the potency to improve efficiency and accuracy in forensic identification in the future.Keyword : sex estimation, forensic odontology, advanced imaging